Al-Takamul al-ma'rifi wa-qadaya al-ta'ṣīl wa-al-tajdid = Integration of knowledge and the issues of originality and renewal - Ahmed Shogar, Ibrahim Adam (IIUM Press, 2013)
This is the first book about integration of modern science. It consists of proceedings of International Conference on Islamization in Modern Science and Scientification of the Studies in Islamic Revealed Knowledge (ICIMSIS), Organized by Kulliyyah of Science, IIUM, on December 2011. The book dicuses various issues on integration of knowledge in Arabic.